ART THINKING THE FANZINE AS A LIBERATING AND CRITICAL DEVICE FOR LEARNING, CATHARSIS AND CULTURAL PRODUCTION. - Martínez Ludert, Edgar (UNIVERSIDAD DE SONORA, 2023)
Art Thinking is an opportunity to transform the way knowledge is built, remodel and shared inside and outside the classroom, is not about producing art, but about using the arts as a methodology. Art is a tool to acquire awareness, a form of thought, a meta-discipline (Camnitzer, 2014) and a playful psychomotor activity (Acaso, 2017). This path and deliberate decision requires tenacious, revolutionary teachers who, for a moment, believe that they can be artists. Today more than ever we need unconventional, open, experimental, playful, generous, even why not, psycho-magical strategies that stimulate in our students a genuine impulse to learn, think and act. In this paper (1) I analyzed how this pedagogical strategy impacts critical-creative thinking and motivation of Higher Education (HE) students in the institution Tecnologico de Monterrey in the northwestern region of Mexico (2) and how a playground (metaspace) and a (3) fanzine can work as a tool (hypothesis) to achieve this aims.